Analysis of the information contained in the labeling of bottled water sold in Asunción – Paraguay, 2023 (Revista Científica UCOM Scientia, 2025)
This research aims to analyze the information contained on bottled water labels, based on the requirements of the National Institute of Food and Nutrition (INAN) and other quality indicators, across a wide range of brands sold in self-service establishments located in Asunción, Paraguay, during the year 2023. A mixed-methods approach was used, with a non-experimental, cross-sectional, and descriptive design, based on structured observation using a checklist in the aisles of three establishments. The results indicate that most bottled water brands comply with the established requirements. However, it is advisable to incorporate additional quality parameters, considering that this is a growing business and that some companies do not certify the quality of their products. It is concluded that the labeling of bottled water sold in Asunción is adequate in some cases; however, in others, it lacks detailed information, which limits consumers’ ability to make informed purchasing decisions.